Bacterias patógenas en infecciones del tracto respiratorio. Servicio Autónomo Hospital Universitario "Antonio Patricio de Alcalá". Cumaná, Estado Sucre - Guzmán L Militza; Albarado I Luzmila; Betancourt José; Medina Belkis (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
Abstract: In orden to determine the frequency of bacterial pathogens in the respiratory tract of children between the ages of 0 - 11 years old who attend the emergency service in the Pediatrics ward at the Autonomous Hospital □Antonio Patricio de Alcalá□ in Cumaná, Sucre state during the period from June to November 2001, 150 samples from children with infections in the respiratory tract were analyzed. The microbiological diagnosis was performed using classical methods to identify the microorganisms in clinical samples. The resistance to antibiotics was determined by the agar dilution technique according to the guidelines of the National Committee for Clinical Laboratory Standards (NCCLS). The upper respiratory tract infections (75.00%) exceeded the lower respiratory tract infections. The main cause for medical consultation was pharyngitis (43.00%), followed by otitis (32.00%) and pneumonia (25.00%), and. 62.00% the samples were positive. The microorganisms most frequent in the upper respiratory tract were Streptococcus B-hemolytic group A (24.49%) and Staphylococcus aureus (16.32%) and in the lower respiratory tract Klebsiella pneumoniae (10.20%). The greater percentage of resistance in the microorganism isolates was for the β-lactamics group. Resumen: Con el propósito de determinar la frecuencia de bacterias patógenas a nivel del tracto respiratorio en niños con edades entre 0 y 11 años que acudieron a la emergencia pediátrica del Servicio Autónomo Hospital Antonio Patricio de Alcalá, Cumaná estado Sucre, durante el período junio 2001 a noviembre 2002, se analizaron 144 muestras de niños con infecciones del tracto respiratorio. El diagnóstico microbiológico se realizó siguiendo los métodos clásicos para el procesamiento de muestras clínicas y la resistencia antimicrobiana por los métodos estándares del National Committee of Clínical Laboratory (NCCLS). Se encontró una mayor frecuencia de infecciones a nivel del tracto respiratorio superior (75,00%). La principal causa de consulta médica fue la faringitis (43,00%), seguido por otitis (32,00%) y neumonías (25,00%). Del total de muestras procesadas 62,00% fueron positivas para cultivo bacteriológico. El microorganismo aislado con mayor frecuencia en el tracto respiratorio superior fue Streptococcus β-hemolítico del grupo A (24,49%) y Staphylococcus aureus (16,32%) y en el tracto respiratorio inferior Klebsiella pneumoniae (10,20%). El mayor porcentaje de resistencia de los microorganismos aislados se presentó para el grupo de los B-lactámicos.